Demographics, employment, and proximity to covid-19 as predictors of preparedness among Taiwanese health social workers. (21st April 2023) - Wu, Yi-Ling; Lin, Tsai-Wen; Yang, Chun-Yi; Wang, Samuel Shih-Chih
ABSTRACT: COVID-19 struck the world violently and cause negative psychological consequences on health professionals. The preparedness of social workers for the pandemic is critical while facing these challenges and pressures. The study aimed to explore what are the roles of demographic, employment, and proximity to Covid-19 in predicting preparedness for the next wave of COVID among social workers in Taiwan. A total of 158 participants were conveniently sampled and multiple regression, univariate analysis, and two-way ANOVA were conducted. The results demonstrated that the demographic and employment variables significantly predicted preparedness, and there were significant differences among demographics on preparedness and an interaction effect between seniority and age. Consequently, middle-aged social workers with junior seniority years may have more difficulties in their preparation for the current situation. The implication of our findings is also discussed.